Establishment of Serratia entomophila in soil from a granular formulation - O'Callaghan, M.; Gerard, F.M. (New Zealand Plant Protection, 2005)
A granular formulation of Serratia entomophila has been developed to improve shelflife and storage characteristics of this bacterium which is used as a microbial control agent of the New Zealand grass grub Bacterial establishment and survival of bacteria released from the granular and liquid formulations were assessed in a laboratory experiment Bacteria were enumerated by dilution plating onto Serratia selective agar Serratia entomophila populations in soil inoculated with granules remained stable in soil for up to five months at a range of soil moisture levels Bacterial numbers declined more rapidly when soil was inoculated with the liquid formulation High numbers of bacteria remained viable in the granules throughout the experiment demonstrating the potential for sustained release of inoculum after application of the biopesticide granules